Entrepreneurship : Successfully Launching New Ventures - Barringer, Bruce R.; Ireland, R. Duane (2025)
Explores the allure of entrepreneurship, teaching you how to successfully launch and grow your own company through a clear and easy 4-step process. Using real business profiles of inspiring young entrepreneurs, the text provides relevant examples that are easily relatable.
Includes index.
Keywords: Entrepreneurship; New business enterprises; Business and Management